WebQuest – odpowiedź na zmiany potrzeb edukacyjnych na przykładzie nauczania języka specjalistycznego - Kic-Drgas, Joanna (Studia Edukacyjne, 2018)
The paper aims to present the possibilities WebQuest gives in the educational context for recognising and catering to individual learners’ needs. The focus of the article is on altering the learning conditions contributing to the deepening diversity of learners’ needs. The use of the example of WebQuest as a teaching tool in LSP (Language for SpecificPurposes) class for monitoring needs, together with a highly personalised teaching process, is analysed. The presented application of WebQuest fillsin the gap in the individualisation of the teaching process.